Mustard plant ash: a source of micronutrient and an adsorbent for removal of 2,4-dichlorophenoxyacetic acid - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
The work highlights the utilization of an agricultural waste mustard plant ash (MPA) as a soil additive and an adsorbent. MPA was characterized by X-ray fluorescence (XRF), energy-dispersive X-ray spectroscopy (EDX), proximate analysis, CHNS analysis, Brunauer-Emmett-Teller (BET) surface area analysis, zeta potential measurements, Fourier transform infrared (FTIR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRF analysis confirmed the presence of CaO (31.35 %), K2O (18.55 %), and P2O5 (6.99 %), all of which act as micronutrients to plants. EDX also confirms high amount of elemental O, Ca, K, and P. The adsorptive ability of MPA was investigated using a commonly used herbicide, 2,4-dichlorophenoxyacetic acid (2,4-D), as a representative chemical. Batch adsorption experiments were conducted to study the effect of different operational parameters such as adsorbent dose, initial 2,4-D concentration, contact time, and temperature on the adsorption process. Data from experiments were fitted to various kinetic and isothermal models. The pseudo-second-order kinetic model was found to show the best fit (R (2) > 0.99), with the highest k (2) value of the order 10(5). Based on the study results, dosage of MPA/hectare for different crops has been recommended for effective removal of 2,4-D. To our knowledge, this is the first study in which MPA has been characterized in detail and investigated for dual applications (as an adsorbent and as a soil additive).